(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This paper examined reasons why sponsored academic staff of Nigerian Tertiary institutions absconded after the completion of their studies abroad. Using secondary data collected from both printed and online publications, the paper identified the following reasons: weak sponsorship agreement, poor salaries, inadequate modern infrastructural facilities, poor working environment, insecurity, poor access to research grant and poor economic outlook as reasons why sponsored academic staff of Nigerian tertiary institutions absconded after the completion of their studies abroad. To address this problems, the paper advance the following policies options. Tertiary Education Trust Fund (TETFund) should direct tertiary institutions to review sponsorship agreement to include the following options. Sponsor tertiary institutions shall be responsible to collect certificate of sponsored academic after graduation. Training institutions whether local or foreign shall be informed to send the certificate of the students to the institutions where the academic came from. Academic who want to stay back after completion of study shall refund 100% of the fund used for the training.